Bio-mathematical analysis for the peristaltic flow of single wall carbon nanotubes under the impact of variable viscosity and wall properties. (February 2017) - Shahzadi, Iqra; Sadaf, Hina; Nadeem, Sohail; Saleem, Anber
Highlights: Exact solution is calculated for the temperature and for the velocity profile. Temperature profile decreases when we add nanoparticle into our base fluid. Increase in stiffness and Grashof number in the channel contributes to decrease in fluid velocity. Symmetry of the curved channel is destroyed due to the curvedness for velocity, temperature and for contour plots. Size of the trapped bolus is smaller for pure blood case as compared to the SWCNTs. Abstract: Objective: The main objective of this paper is to study the Bio-mathematical analysis for the peristaltic flow of single wall carbon nanotubes under the impact of variable viscosity and wall properties. Design/approach: The right and the left walls of the curved channel possess sinusoidal wave that is travelling along the outer boundary. The features of the peristaltic motion are determined by using long wavelength and low Reynolds number approximation. Exact solutions are determined for the axial velocity and for the temperature profile. Findings: Graphical results have been presented for velocity profile, temperature and stream function for various physical parameters of interest. Symmetry of the curved channel is disturbed for smaller values of the curvature parameter. It is found that the altitude of the velocity profile increases for larger values of variable viscosity parameter for both the cases (pure blood as well as single wall carbon nanotubes). It is detected that velocity profile increases with increasing values of rigidity parameter. It is due to the fact that an increase in rigidity parameter decreases tension in the walls of the blood vessels which speeds up the blood flow for pure blood as well as single wall carbon nanotubes. Increase in Grashof number decreases the fluid velocity. This is due to the reason that viscous forces play a prominent role that's why increase in Grashof number decreases the velocity profile. It is also found that temperature drops for increasing values of nanoparticle volume fraction. Basically, higher thermal conductivity of the nanoparticles plays a key role for quick heat dissipation, and this justifies the use of the single wall carbon nanotubes in different situations as a coolant. Conclusions: Exact solutions are calculated for the temperature and the velocity profile. Symmetry of the curved channel is destroyed due to the curvedness for velocity, temperature and contour plots. Addition of single wall carbon nanotubes shows a decrease in fluid temperature. Trapping phenomena show that the size of the trapped bolus is smaller for pure blood case as compared to the single wall carbon nanotubes.